Formulating Adaptive Islamic Education Policies: Conservative Resilience of Salafi Dayah Amid Digital Disruption - Zainuddin Zainuddin; Syamsul Rizal; Samsuar Samsuar; Mohd Nasir; Rita Sari (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to reinterpret the resilience of Salafi dayah in Aceh in facing the digital era, not as an absolute rejection of modernization, but as a conservative pedagogical strategy that preserves the continuity of Islamic knowledge, the authority of the teungku, communal discipline, and the tradition of kitab kuning. This study employs a qualitative ethnopedagogical approach by combining field observations, interviews with teungku and santri, and an examination of curriculum documents, learning routines, and disciplinary practices within the dayah environment. The findings indicate that the conservative resilience of Salafi dayah is formed through five main mechanisms: a curriculum orientation rooted in inherited traditions, the preservation of bale beut and the bandongan-sorogan methods, moral formation through bodily discipline, the charismatic legitimation of the teungku, and the selective use of digital technology. Salafi dayah do not entirely reject change; rather, they negotiate digital disruption by distinguishing technologies that support da‘wah and scholarly references from those that may weaken adab, concentration, and communal obedience. Thus, conservatism in Islamic education can be understood as a reflective form of cultural defense, rather than mere stagnation.